PENGARUH KUALITAS PRODUK, DAYA TARIK IKLAN TERHADAP MINAT BELI PRODUK INDOMIE (STUDI KASUS PADA MASYARAKAT DI BEKASI) - Nurul Aisyah (Universitas Bina Sarana Informatika, 2015)
This research aims to know whether the quality of products , attractiveness advertising influences interest of consumers purchasing products indomie in bekasi .The problems have been identified that the purchase of products applied with need or purposes , especially in the area that is learned. To know the interest of interest buy indomie held a hypothesis about the influence of product quality and attractiveness advertising .A factor that affects interest buy on the writing of this restricted with two variables affecting purchasing interest namely product quality and attractiveness iklani .For the purposes of research sample taken 100 consumers indomie that has been selected in the area that is learned .This research using regression technique used to analyze data , and spss was also used in analyzed data. The method used was quantitative. Used to examine the population or certain sample.Of the sample done by means of random, the collection of data and the use of a particular, research analysis of quantitative data and statistics which aims to test the hypothesis that has been decided.The result indicates that it is good enough and the variables of product quality and power tariki ad shows a significant and positive effect on interest to buy products indomie.Keywords: quality of product, advertising appeal, willingness to buy.